Busana Pengantin Wanita Modifikasi Kebaya dari Indonesia dan Lehenga dari India - Mien Zyahratil Umami; Riris Kesawamurti Anggarani (Garina, 2021)
The bridal clothing modification kebaya and lehenga is expected to be an innovation in fashion products and can increase the variety of bridal clothing. The objectives of this study is to knowing the process of making modified bridal dress Kebaya from Indonesia and Lehenga from India. The method used in this research is the R&D method (Research and Development), literature, questionnaires, and documentation. The making of Modified Bridal Dress Kabaya and Lehenga was carried out at the Fashion Laboratory of the Fashion Design Study Program of the Kartini Academy of Social Welfare, st. Sultan Agung, No. 77 Gajah Mungkur Village, Gajah Mungkur District, Semarang City. Data analysis in this research was carried out using descriptive analysis. The result of this research is the kebaya as the superior of the lehenga which is equipped with chunri (shawl). The process of making this modified bridal dress Kabaya and Lehenga includes designing, measuring, making patterns, cutting materials, sewing material that has been patterned or cut, set the application, and finishing by sequencing the Lehenga and kebaya.